University Babylon : film and race politics on campus - Marez, Curtis (University of California Press, 2020)
"From the silent era to the present, film productions have shaped the way the public views campus life. Mediating representations of higher education, collaborations between Hollywood entities and universities have disseminated influential ideas of race, gender, class, and sexual difference. Even more directly, Hollywood has drawn writers, actors, and other talent from ranks of professors and students while also promoting the industry in classrooms, curricula, and film studies programs. In addition to founding film schools, university administrators have offered campuses as filming locations. In University Babylon, Curtiz Marez argues that cinema has been central to the uneven incorporation and exclusion of different kinds of students, professors, and knowledge. Working together, Marez argues, film and educational institutions produced a powerful ideology that linked respectability to academic merit in order to manage and profit from people of color. Combining concepts and methods from critical university studies, ethnic studies, native studies, and film studies, University Babylon analyzes the symbolic and institutional collaborations between Hollywood filmmakers and university administrators over the representation of students and, by extension, of college life more broadly"--Provided by publisher.